Nature as Defiant Hope in “As Long as the Lemon Trees Grow” by Zoulfa Katouh - Sindi Ayu Amelia; Henrikus Joko Yulianto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This article studies the symbiotic relationship between ecological health and psychological resilience in Zoulfa Katouh’s ‘As Long as the Lemon Trees Grow’ (2022) through the lens of ecopsychology by Theodore Roszak’s (1992) theoretical framework. The study first examines how the environmental degradation of Syria depicts the mental state of the human psychology through collusive madness that causes environmental destruction which also inflicts severe pain on humans. On the other hand, this research exposes the healing process, it highlights the importance of reconnecting with nature to reshape human well-being. The practical of Salama’s technique to reconnect with nature is being studied at the end of the research. She uses botanical grounding which is murmuring medicinal plant names like sweet alyssum and lavender system during terrifying moments to relax herself while controlling her breath. Finally, the article exposes the lemon tree as the definitive symbol of "defiant hope." By looking at Salama’s journey from the rubble of Homs to her balcony garden in Toronto, this research examines that planet and human cannot be separated as these two share health as what Roszak called a single continuum.